Pengabdian Peningkatan Nilai Produk Dengan Pengelolaan Biaya dan Margin di PT Tentang Anak Bahagia - Dewi Agustina; Irwanto Handojo; Kartina Natalilova (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2026)
This community service program aimed to enhance participants' competencies in cost management and margin optimization at PT Tentang Anak Bahagia through an analytical approach covering cost classification, cost driver management, contribution margin analysis, and break-even point analysis. The program was conducted on April 30, 2026, involving 26 participants consisting of company employees and management personnel. The methods employed included interactive lectures, case study discussions, and direct question-and-answer sessions related to the company's operational conditions. Prior to the training, participants completed a questionnaire indicating that their theoretical understanding of cost, value, and margin management was still limited, with an average score of 71.25. Following the training and intervention, a significant improvement was observed, with the average score increasing to 92.92. Statistical analysis using SPSS revealed a moderate correlation between pre-test and post-test scores (r = 0.489, p = 0.015) and a statistically significant difference between scores before and after the training (t = -9.737; p < 0.001). These findings indicate that the training was effective in significantly improving participants' understanding, as evidenced by the consistent and statistically significant increase in scores. Overall, the program successfully strengthened competencies in cost management, margin optimization, and data-driven strategic decision-making, thereby supporting the company's sustainability and long-term growth.